Fishing boats at anchor, skiff with people, at Fisherman's Wharf - Albert Walton DeRome:::Creator::::::::::::
Large purse seiners, lamparas at anchor, skiff with people walking in the foreground, at Harbor Wharf number 2, Fisherman's Wharf, near Booth's Cannery in Monterey, California. The photographer, Albert Walton DeRome (Al Aagard), was a cousin of Carol Henning Steinbeck. (see Steinbeck Studies 15.1 (2004): 18.)